Barriers to Physical Education Teachers in Writing Scientific Papers at SMK Sekota Bengkulu - Bayu Dirgantara; Martiani Martiani; Juwita Juwita (Penerbit Jurnal Indonesia, 2021)
This study aims to determine the barriers of Physical Education teachers in writing scientific papers at SMK Sekota Bengkulu. This research is a quantitative descriptive research with one shot case study method. The population in this study were Physical Education teachers at the Bengkulu City Vocational School, which amounted to 15 teachers. Sampling used a total sampling consisting of 15 teachers. The instrument used in the form of a teacher's questionnaire about physical education teachers' obstacles in writing scientific papers at SMK in Bengkulu city. The instrument in the form of a teacher questionnaire used has been validated by researchers with expert validation. The data analysis technique used is a quantitative descriptive analysis technique with percentages. The results showed that the physical education teacher's obstacles in writing scientific papers at SMK Sekota Bengkulu in the physical education teacher questionnaire with a comprehensive category that limited time in writing scientific papers with a percentage of 67% chose the answer YES while 33% chose the answer no. Then the category of lack of motivation in scientific writing with a percentage of 73% choosing the answer YES while 27% who chose the answer no. Furthermore, the category of lack of understanding in writing scientific papers with a percentage of 67% chose the answer YES while 33% chose the answer no.